(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2019)
The experiments showed that the 3-azolylcoumarins and furo[3,2-g]coumarins coumarin cycle’s opening occurs only in aqueous alkali, and when alkylated in an organic solvent in the presence of K2CO3, the lactone fragment remains unchanged. The 7-hydroxy-6-(isocoumarin-3-yl)-4-methylcoumarin cycle turned out to be more labile. The result of alkylation of this compound with ethyl acetate of chloroacetic acid in the presence of K2CO3 depended on the nature of the aprotic solvent and the temperature of reaction. So, when this reaction was carried out in boiling acetone, only the free hydroxyl group at position 7 of coumarin was alkylated. But when the initial coumarin was heated at 100 °С with an excess of an alkylating agent in DMSO, simultaneous alkylation of both the free 7-OH group and the endocyclic Oxygen atom occurred.